Organizational communication as the challenge in the management of Russian schools - Sazonova, Diana (My University, 2016)
Communication is an inevitable process in the workplace. Through communication it is possible to give tasks, control, and support, appreciate and recognize the achievements and so on. Thus an effective communication at work leads to the overall success of the organization. For many years Russian public organizations were highly centralized and employees were not involved in the decision-making processes. The managers did not consider internal communication as an important aspect of work. Many years have passed since the collapse of the USSR and it was of significant interest to investigate if the organizational communication was developed. Therefore, the main aim of this study was to examine the internal communication in Russian schools to date. To reach this goal, it was necessary to define the organizational communication, examine the types of organizational communication and directions of information flow, and analyze the barriers to effective communication and ways of their elimination. Qualitative method of research was chosen as a method of research. The face-to-face interviews were made with 15 employees of three Russian schools. Direct communication gave an opportunity to get detailed and pithy information. Such method clearly showed that internal communication in Russian public schools is still not very developed. Internal communication needs to be improved by the better involvement of employees in the organizational processes, improvement of the leadership style, and active application of methods preventing from communication barriers.
Keywords: organizational communication; schools; management; public sector; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|